Pengaruh Psychological Well-Being terhadap Work Engagement pada Karyawan Direktorat Operasional - Tsabita Putri Islamy; Widawati, Lisa (Jurnal Riset Psikologi, 2023)
Abstract. Psychological well-being is the level of happiness achieved in the absence of psychological disorders, which is indicated through the ability of individuals to maximize their psychological functioning (Ryff, 1989). Work engagement is an appreciation followed by positive thinking and feelings of fulfillment related to work (Schaufeli et al., 2002). This study aims to examine the influence of psychological well-being on work engagement in employees of the operational directorate of PTPN VIII Ciater. This study uses a causality quantitative approach with cross-sectional data and multiple regression analysis techniques. A total of 59 employees of the operational directorate of PTPN VIII Ciater were selected as subjects in this study. The measuring instruments used were Ryff's Psychological Well-Being Scale (RPWB) developed by Ryff (1989) and adapted by Fadhil (2021) and the Utrecht Work Engagement Scale (UWES) developed by Schaufeli and Bakker (2004) and adapted by Aryanti et al. (2020). The results showed that 81.4% of employees have high psychological well-being and 86.4% of employees have high work engagement. Psychological well-being has a positive influence on work engagement by 94.2%. All dimensions of psychological well-being have a positive influence on work engagement. Abstrak. Psychological well-being adalah tingkat kebahagiaan yang dicapai dengan tidak adanya gangguan psikologis, yang diindikasikan melalui kemampuan individu untuk memaksimalkan fungsi psikologisnya (Ryff, 1989). Work engagement yaitu penghayatan yang diikuti dengan pemikiran positif dan perasaan terpenuhi yang berhubungan dengan pekerjaan (Schaufeli et al., 2002). Penelitian ini bertujuan untuk menguji pengaruh psychological well-being terhadap work engagement pada karyawan direktorat operasional PTPN VIII Ciater. Penelitian ini menggunakan pendekatan kuantitatif kausalitas dengan data cross-sectional dan teknik analisis regresi berganda. Sebanyak 59 karyawan direktorat operasional PTPN VIII Ciater dipilih menjadi subjek pada penelitian ini. Alat ukur yang digunakan adalah Ryff's Psychological Well-Being Scale (RPWB) yang dikembangkan oleh Ryff (1989) dan kemudian diadaptasi oleh Fadhil (2021) serta Utrecht Work Engagement Scale (UWES) yang dikembangkan oleh Schaufeli dan Bakker (2004) dan kemudian diadaptasi oleh Aryanti et al. (2020). Hasil penelitian menunjukkan bahwa 81.4% karyawan memiliki psychological well-being yang tinggi dan 86.4% karyawan memiliki work engagement yang tinggi. Psychological well-being memberikan pengaruh positif pada work engagement sebanyak 94.2%. Keseluruhan dimensi psychological well-being memberikan pengaruh positif terhadap work engagement.